A Pilot Study of Switching Electroconvulsive Therapy for Patients With Treatment Resistant Schizophrenia or Mood Disorder. Issue 3 (September 2021) - Tan, Xiao Wei; Oon, Li Keat; Tsang, Yun Ying Tammy; Ong, Hatta Santoso; Tor, Phern Chern
Abstract : Objectives: Switching of ECT electrode modality is commonly done in clinical practice but outcomes are unclear. We aimed to compare the clinical outcomes between ECT modality switchers and nonswitchers in a large tertiary psychiatric institution over 1 year. Methods: Brief Psychiatric Rating Scale (BPRS), Montgomery–Åsberg Depression Rating Scale (MADRS) and Montreal Cognitive Assessment (MoCA) were used to assess symptoms and cognition. General linear regression was utilized to compare the change of BPRS or MADRS and MoCA score among switchers vs nonswitchers. Results: 21.5% of 209 patients switched ECT. Baseline BPRS scores were lower among nonswitchers. Response rate in schizophrenia, depression and mania were higher for nonswitchers (69.6%, 81.35% and 84.8% respectively / 9.2 (SD 3.3) sessions) compared to switchers (53.8%, 0% and 66.7% respectively / 10.6 (SD 4.5) sessions). Most common ECT switches were Bifrontal (BF) to Bitemporal (BT) (schizophrenia), UB RUL (ultrabrief right unilateral) to BT (depression), and UB RUL to BT / BF (mania). There was no significant difference in the change of BPRS and MoCA scores between nonswitchers and switchers. However, there was significantly more improvement of MADRS scores among nonswitchers [adjusted mean ± SE: (−26.4 ± 2.8)] compared with switchers (−10.6) ±6.6). Conclusions: ECT switching was commonly done and may result in better or worse outcomes than not switching depending on diagnosis. Controlled trials are required to address this urgent clinical issue.